The Long Pentraxin PTX3 Controls Klebsiella Pneumoniae Severe Infection - Asgari, Fatemeh; Supino, Domenico; Parente, Raffaella; Polentarutti, Nadia; Stravalaci, Matteo; Porte, Remi; Pasqualini, Fabio; Barbagallo, Marialuisa; Perucchini, Chiara; Recordati, Camilla; Magrini, Elena; Mariancini, Andrea; et al. (Frontiers in Immunology, 2021)
Klebsiella pneumoniae is a common pathogen in human sepsis. The emergence of multidrug-resistant K. pneumoniae strains represents a major clinical challenge in nosocomial and community acquired infections. The long pentraxin PTX3, a key component of humoral innate immunity, is involved in resistance to selected pathogens by promoting opsonophagocytosis. We investigated the relevance of PTX3 in innate immunity against K. pneumoniae infections using Ptx3-/- mice and mouse models of severe K. pneumoniae infections. Local and systemic PTX3 expression was induced following K. pneumoniae pulmonary infection, in association with the up-regulation of TNF-a and IL-1β. PTX3 deficiency in mice was associated with higher bacterial burden and mortality, release of pro-inflammatory cytokines as well as IL-10 in the lung and systemically. The analysis of the mechanisms responsible of PTX3-dependent control of K. pneumoniae infection revealed that PTX3 did not interact with K. pneumoniae, or promote opsonophagocytosis. The comparison of susceptibility of wild-type, Ptx3-/-, C3-/- and Ptx3-/-/C3-/- mice to the infection showed that PTX3 acted in a complement-independent manner. Lung histopathological analysis showed more severe lesions in Ptx3-/- mice with fibrinosuppurative, necrotizing and haemorrhagic bronchopneumonia, associated with increased fibrin deposition in the lung and circulating fibrinogen consumption. These findings indicate that PTX3 contributes to the control of K. pneumoniae infection by modulating inflammatory responses and tissue damage. Thus, this study emphasizes the relevance of the role of PTX3 as regulator of inflammation and orchestrator of tissue repair in innate responses to infections.